Pertanggungjawaban Pidana Terhadap Tindak Pidana Korupsi Dana Hibah (Studi Kasus Putusan No. 81/Pid.sus-TPK/2019/PN.MKS) - Ulfa Dian Ushari; Kamri Ahmad; Azwad Rachmat Hambali (Qawanin Jurnal Ilmu Hukum, 2020)
Corruption is the root of all national problems and is the main cause of poverty. Corruption can bring down a regime and even torment a nation. In various parts of the world, corruption always gets more attention compared to other criminal acts. Corruption is a serious problem, this crime can endanger the stability and security of society. Corruption in Indonesia continues to show an increase from year to year. Corruption cases are difficult to disclose because the perpetrators use sophisticated equipment and are usually carried out by more than one person in covert and organized circumstances. In government agencies have an obligation to create good governance in financial management that is accountable, open and responsible, so as an effort to create transparency and accountability is the arrangement of accountability for the use of an accurate and acceptable budget, but sometimes someone has this responsibility. instead abusing his power. One of the things that happened in Makassar City was corruption related to the Grant Funds carried out by the secretary of the General Election Commission (KPU) during the election of the Mayor and Deputy Mayor in 2018.